Reduction of Environmental Distraction to Facilitate Cognitive Performance - Timothy John Hollins (Frontiers Research Topics, 2015)
When faced with a difficult task, people often look at the sky or close their eyes. This behavior is functional: the reduction of distractions in the environment can improve performance on cognitive tasks, including memory retrieval. Reduction of visual distractions can be operationalized through eye-closure, gaze aversion, or by comparing exposure to simple and complex visual displays, respectively. Reduction of auditory distractions is typically examined by comparing performance under quiet and noisy conditions. Theoretical reasoning regarding this phenomenon draws on various psychological principles, including embodied cognition, cognitive load, and modality-specific interference. Practical applications of the research topic are diverse. For example, the findings could be used to improve performance in forensic settings (e.g., eyewitness testimony), educational settings (e.g., exam performance), occupational settings (e.g., employee productivity), or medical settings (e.g., medical history reporting). This Research Topic welcomes articles from all areas of psychology relating to the reduction of distractions to improve task performance. Articles can address (but are not limited to) new empirical findings, comprehensive reviews, theoretical frameworks, opinion pieces, or discussions of practical applications.